A highly selective balanced wideband bandpass filter based on nested split‐ring resonators. Issue 10 (17th June 2019) - Xu, Le; Wang, Zan Xian; Wei, Feng; Li, Rui; Zou, Xin T.
Abstract: A balanced wideband bandpass filter (BPF) with a high frequency selectivity, controllable bandwidth, and good common‐mode (CM) suppression based on nested split‐ring resonators (SRRs) is proposed in this article. The proposed nested SRRs are applied to form three transmission poles (TPs) that can achieve a wide differential‐mode (DM) passband centered at 3.0 GHz. Meanwhile, two transmission zeros (TZs) are generated to realize a high frequency selectivity of the DM passband. Moreover, TPs and TZs can be quasi‐independently controlled by changing the physical lengths of SRRs and the gaps between them, which can greatly improve the flexibility and practicality of the design. The proposed balanced BPF is fed by balanced microstrip‐slotline (BMS) transition structures. For the CM signals, the BMS transition structures can achieve a good wideband CM suppression without affecting the DM ones, thereby simplifying the design procedure. In order to validate its practicability, a balanced wideband BPF is fabricated and a good agreement between the simulated and measured results is obtained.